REVIEW OF DOWNSCALING METHODS FOR CLIMATE CHANGE IMPACTS ON WATER RESOURCES (Malaysian Journal of Civil Engineering, 2018)
Measuring the impact of climate change on water resources is commonly based on downscaled simulations from global climate models (GCMs). The downscaling of GCMs is used to improve representation of climate data over a regional part which can be produced either by using a regional climate model (RCM) or statistical downscaling. Although both of these two techniques are common, but they are seldom compared. This study review the relationship between climate change and water resources, impact of climate change on hydrological system, and the discussion on several downscaling methods that are commonly used in the assessment of climate change impacts on water resources. Past studies have shown that climate change will directly affect water resources, and will result to increase or decrease of the water body on earth surface. This study found that statistical downscaling technique is more favourable and more efficient technique to assess the climate change impacts on water resources. However, it is still not clear which methods can give the most reliable estimates of projected climate change, since the modelling procedures of GCMs have their own strengths and limitations.